TINGKAT KECEMASAN IBU HAMIL DAN KEPATUHAN KUNJUNGAN ANTENATAL CARE DI MASA PANDEMI PUSKESMAS ADIMULYO KEBUMEN - Wahidah Agusmiasari; Tin Utami; Siti Haniyah (Jurnal Cakrawala Ilmiah, 2023)
Background: One of the vulnerable groups infected with COVID-19 is pregnant women, when pregnant there are physiological changes that result in decreased immunity. In addition, COVID-19 is easy to spread, causing anxiety, including pregnant women. Pregnant women are at a higher risk of experiencing anxiety and depression since the emergence of COVID-19. Anxiety in pregnant women has a bad impact and prevention efforts in a healthy pregnancy are antenatal care. Objective: this study was to determine the level of anxiety of pregnant women and adherence to antenatal care during the pandemic. Methods: This study uses quantitative research methods. The research design used cross sectional approach. The sampling technique used is the Nonprobability Sampling technique with total sampling. Respondents in this study were 44 respondents. Results: The results showed that pregnant women did not experience anxiety as many as 16 respondents (36.4%). Compliance with antenatal care visits found that 39 respondents (88.6%) were obedient and 5 respondents (11.4%) did not comply. Conclusion: The majority of pregnant women do not experience anxiety and are obedient in conducting antenatal care visits.